Gender, Subsistence, Change, and Resilience in Quinhagak’s Present and Past - Sloan, Anna C. (Études/Inuit/Studies, 2019)
Like many other Alaska Native communities, the Yup’ik people of Quinhagak follow a subsistence lifestyle that is multi-faceted, socially embedded, and specifically tailored to the land and water on which it is practiced. This paper provides a synthesis of Quinhagak residents’ perspectives on subsistence in both the present and the past, as documented in original interviews and in the literature, with a focus on how gendered social identities are enacted through these traditions. The Nunalleq site presents a unique opportunity to examine the time depth of local subsistence lifeways and their social iterations, as well as how these were affected by changing landscapes and climate—all realities of contemporary Quinhagak life, just as they were for the ancestors at Nunalleq. The interrelation of subsistence and sociality has implications for how we understand Yup’ik resiliency and survivance in the face of such changes. Comme beaucoup d’autres communautés des Premières Nations de l’Alaska, les Yupiit de Quinhagak ont un mode de subsistance à « multi-facettes », socialement intégré et spécifiquement adapté à la terre et à l’eau dans lesquels ils sont pratiqués. Cet article propose une synthèse des perspectives de subsistance des résidents de Quinhagak, à la fois dans le présent et dans le passé, documentée à partir des entrevues originales et de la littérature axées sur les identités sociales de genres établies à ravers ses traditions. Le site Nunalleq offre l’unique opportunité d’exminer en profondeur les modes de subsistance dans le temps et leurs interactions sociales, ainsi que la manière dont les changements du climat et des paysages en sont affectés – toutes les réalités de la vie contemporaine à Quinhagak. Juste comme elles étaient pour leurs ancêtres à Nunalleq. L’inter-relation de la subsistance et de la société a eu des implications sur la manière dont nous comprenons la résilience et la survit des Yupiit face à de tels changements.